Gone by midnight - Fox, Candice (New York : Forge, 2020)
"Crimson Lake is where people with dark pasts come to disappear-and where others vanish into thin air... Four young boys are left alone in a hotel room while their parents dine downstairs. When Sara Farrow checks on the children at midnight, her son is missing. Distrustful of the police, Sara turns to Crimson Lake's unlikeliest private investigators-disgraced cop Ted Conkaffey and convicted killer Amanda Pharrell. For Ted, the case couldn't have come at a worse time. Two years ago a false accusation robbed him of his career, his reputation, and most importantly, his family. But now Lillian, the daughter he barely knows, is coming to stay in his ramshackle cottage by the lake. Ted must dredge up the area's worst characters to find the missing boy. The clock is ticking, and the danger he uncovers could well put his own child in deadly peril"--
"A Tom Doherty Associates book."
"Previously published by Bantam Australia in trade paperback in January 2019."
Keywords: Private investigators -- Fiction; Missing children -- Fiction; Queensland -- Fiction; Detective and mystery fiction; Thrillers (Fiction)